Original articleCorticobasal degeneration – clinico-pathological considerations - Kłodowska-Duda, Gabriela; Słowiński, Jerzy; Opala, Grzegorz; Gorzkowska, Agnieszka; Jasińska-Myga, Barbara; Wszołek, Zbigniew K.; Dickson, Dennis W. (Folia Neuropathologica, 2006)
Corticobasal degeneration (CBD) is a rare sporadic 4-repeat tauopathy. We report here the first Polish case of pathologically proven CBD. Our patient developed clumsiness of the right hand at age 63 years. During the course of his illness he suffered from progressive asymmetric parkinsonism unresponsive to dopaminergic therapy. Focal dystonia affecting right upper extremity, non-fluent aphasia, dysphagia, supranuclear vertical gaze palsy, imbalance and myoclonus ensued. The patient died of pneumonia at age 71 years. Head magnetic resonance imaging revealed the presence of asymmetric cortical atrophy contralateral to the clinically more affected right side. Median somatosensory evoked potentials performed bilaterally demonstrated significant reduction of cortical evoked potential amplitudes recorded from the left scalp electrodes. Neuropathological examination showed cortical atrophy of the frontal and parietal lobes with superficial spongiosis and diffuse cortical gliosis. Numerous ballooned neurons were found in frontal and parietal cortices. The most remarkable pathology was extensive tau-immunoreactivity of glial and neuronal cell processes, significantly pronounced in the frontotemporal cortex, basal ganglia, thalamus and brainstem. Recent research studies have resulted in better clinical, pathological and genetic characterization of sporadic tauopathies. It is hoped that similar progress will ensue in the development of symptomatic and eventually curative treatments for these rare conditions.